2005
DOI: 10.1002/ar.b.20062
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of computer‐assisted instruction in histology: Effect of interaction on learning outcome

Abstract: The purpose of this study was to determine better strategies for the design and use of computer-assisted instruction (CAI) in health science subjects that require visual learning. Evaluation of current use of CAI was focused on three CD-based modules developed to teach histological images to beginning medical students at multiple sites. For internal control, students' learning outcomes and perceived effectiveness were analyzed with their demographic characteristics, computer attitude, computer experience, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 14 publications
(15 reference statements)
1
29
0
2
Order By: Relevance
“…First, those that incorporate static images, such as slide projections, virtual laboratories on CD-ROM, web pages, and Computer-Assisted Instruction (CAI) where students learn by themselves guided by the program sites (Lei et al, 2005;Michaels et al, 2005;Blake et al, 2003;Bloodwood & Ogilvie, 2006). For years researchers have attempted to compare the effects of medical CAI with traditional media (lectures, laboratory experiences, textbooks), but they are usually difficult to perform properly because variables such as differences in pedagogical techniques, differences in informational content, and the novelty factor have commonly not been controlled adequately (Lei et al).…”
Section: Introductionmentioning
confidence: 99%
“…First, those that incorporate static images, such as slide projections, virtual laboratories on CD-ROM, web pages, and Computer-Assisted Instruction (CAI) where students learn by themselves guided by the program sites (Lei et al, 2005;Michaels et al, 2005;Blake et al, 2003;Bloodwood & Ogilvie, 2006). For years researchers have attempted to compare the effects of medical CAI with traditional media (lectures, laboratory experiences, textbooks), but they are usually difficult to perform properly because variables such as differences in pedagogical techniques, differences in informational content, and the novelty factor have commonly not been controlled adequately (Lei et al).…”
Section: Introductionmentioning
confidence: 99%
“…The desired feature for instructional interaction ranged from a cue that would draw the attention of the user to key histological structures and providing descriptions to a low-risk testing with instant feedback. Interactive features on an online course were reported to significantly improve students' scores on examination when compared to an e-course without interactive features [15,16]. In a study conducted by Lei et al, students reported that interactive features were essential in their learning experience [16], which quantitatively corresponded to improved exam performance.…”
Section: Discussionmentioning
confidence: 93%
“…Students also rated the impact of the interactive LDI and the review material in CD format very highly in a formative evaluation conducted after the introduction of this system into the laboratory. This indicates that the majority of the students who highly valued this interactive LDI learning approach truly learned from it (Lei et al, 2005). Initial student resistance that usually accompanies introduction of nontraditional and active learning based methodology (Lunsford and Herzog, 1997) was not seen in response to the LDI system, probably due to its simplicity and the apparent immediate outcome in understanding the subject and the underlying unity of the form and function concept.…”
Section: Discussionmentioning
confidence: 95%